Can Portland cement be replaced by low-carbon alternative materials? A study on the thermal properties and carbon emissions of innovative cements. (10th June 2018) - Maddalena, Riccardo; Roberts, Jennifer J.; Hamilton, Andrea
Abstract: One approach to decarbonising the cement and construction industry is to replace Portland cement systems with lower carbon alternatives that have suitable properties. We show that seven cementitious binders comprised of metakaolin, silica fume and nano-silica have improved thermal performance compared with Portland cement and we calculate the full CO2 emissions associated with manufacture and transport of each binder for the first time. Due to their high porosity, the thermal conductivity of these novel cements is 58–90% lower than Portland cement, and we show that a thin layer (20 mm), up to 80% thinner than standard insulating materials, is enough to bring energy emissions in domestic construction into line with the UK 2013 Building Regulations. Carbon emissions in domestic construction can be reduced by c . 20–50% and these cementitious binders are able to be recycled, unlike traditional insulation materials. Graphical abstract: Image 1 Highlights: Green cements high in porosity and very low in thermal conductivity are developed. They are a low-carbon alternative to traditional insulation materials and mortars. A simplified GHG emissions estimation method has been proposed in the UK context.